Engineered mesenchymal stromal cells with interleukin-1beta sticky-trap attenuate osteoarthritis in knee joints - Kim, Christopher; Li, Biao; Nakamura, Sayaka; Neely, Eric J.; Rockel, Jason S.; Oussenko, Tatiana; Zhang, Puzheng; Kapoor, Mohit; Nagy, Andras (Frontiers in Cell and Developmental Biology, 2025)
Osteoarthritis (OA) is a common chronic inflammatory joint disease, in which innate immunity plays a pivotal role in pathogenesis. Anti-interleukin-1(IL-1) therapies have shown inconsistent results in clinical trials, potentially due to a mismatch in the spatial and temporal dynamics of interleukin-1beta (IL-1β) production and therapeutic interventions. To address this issue, we developed a novel IL-1β “sticky-trap” utilizing cell and gene-based technologies from our lab and evaluated its efficacy in reducing osteoarthritis progression using a murine destabilization of the medial meniscus (DMM) OA model and a compact bone-derived mesenchymal stromal cell (MSC)-based gene expression system. The extracellular domain of interleukin-1 receptor 2 (IL1R2) was employed to design the sticky IL1R2 trap (stkIL1R2). A murine compact bone-derived MSC line was engineered for gene delivery. Although stkIL1R2 was undetectable in the engineered MSC supernatants by enzyme-linked immunosorbent assay (ELISA) and Western blot, it was localized on the cell surface and extracellular matrix (ECM) and demonstrated specific binding to IL-1β using a fluorescent protein-fused binding assay. Doxycycline (Dox)-induced expression of stkIL1R2 significantly inhibited lipocalin-2 (LCN2) expression which is a biomarker of IL-1β activity. For in vivo experiments, 5 × 104 Dox-inducible stkIL1R2f expressing MSCs were injected into the knee joints of DMM mice. Bioluminescence imaging revealed MSC survival in the knee joints for up to 7 weeks post-injection. Histological analyses at 10 weeks post-injection, including Safranin-O and Masson trichrome staining, showed that stkIL1R2 treated joints exhibited significantly less cartilage degradation and synovitis compared to controls, as assessed by Osteoarthritis Research Society International (OARSI) scoring of the femur, tibia, and synovium. Moreover, stkIL1R2 treatment reduced matrix metalloproteinases-13 (MMP-13) positive cells and collagen type II degradation in the affected joints. In conclusion, we developed a MSC line expressing an inducible IL1 sticky-trap, which localized to the cell surface and ECM and specifically bound IL-1β. These engineered MSCs survived in normal and DMM knee joints for up to 7 weeks and significantly delayed OA progression and inflammation in the murine model. This study introduces a promising therapeutic approach to combat OA progression.